"The terrible dryness woke me up, I had some trouble breathing"—Critical situations related to oral health as described by CPAP‐treated persons with obstructive sleep apnea. (28th June 2022) - Ahonen, Hanna; Broström, Anders; Fransson, Eleonor I.; Neher, Margit; Lindmark, Ulrika
Summary: Continuous positive airway pressure is a common and effective treatment for obstructive sleep apnea, but adherence remains an issue. Both obstructive sleep apnea and oral diseases are associated with cardiovascular diseases, and as oral dryness contributes to treatment abandonment, oral health is of importance for this patient group. The aim was therefore to explore how persons with continuous positive airway pressure‐treated obstructive sleep apnea experience situations associated with their oral health, and which actions they take to manage these. An explorative and descriptive design was adopted using the critical incident technique. Based on a purposeful selection, 18 adults with long‐term experience of continuous positive airway pressure‐treatment were interviewed using a semi‐structured interview guide. Both negative and positive situations were described. Negative situations consisted of challenges with breathing, including mouth‐breathing, choking sensations, problems with night‐time and daytime oral dryness, changes in the saliva composition, and deteriorating oral health. Positive situations included experiences of reduced mouth‐breathing and oral dryness. The situations were often successfully managed by mimicking daytime movements, changing sleeping position, adjusting the CPAP‐device and mask, increasing oral hygiene efforts, drinking water, using a humidifier or chinstrap, or contacting their oral healthcare clinic. Long‐term experience of persons with continuous positive airway pressure‐treated obstructive sleep apnea regard situations and actions from everyday life. Successful management can contribute to long‐term adherence and decrease negative effects on oral health. More interdisciplinary collaborations could enable identification and adequate recommendations for persons who experience negative situations during their continuous positive airway pressure treatment.